Eye Movements Reveal the Spatiotemporal Dynamics of Visual Search - Zelinsky, Gregory J; Rao, Rajesh P N.; Hayhoe, Mary M; Ballard, Dana H. (Psychological Science, 1997)
Given that attention precedes an eye movement to a target it becomes possible to use fixation sequences to probe the spatiotemporal dynamics of search Applying this method to a realistic search task, we found eye movements directed to the geometric centers of progressively smaller groups of objects rather than accurate fixations to individual objects in a display Such a binary search strategy is consistent with zoom-lens models positing an initially broad distribution of search, followed by a narrowing of this search region until only the target is selected We also interpret this oculomotor averaging behavior as evidence for an initially parallel search analysis that becomes increasingly serial as the search process converges on the target